THE INSTITUTION OF PRESIDENCY IN THE CENTRAL ASIAN COUNTRIES: PERSONALIZATION VS. INSTITUTIONALIZATION - BORISOV, Nikolay (CENTRAL ASIA AND THE CAUCASUS, 2011)
Much has been written about the institution of presidency and its traps, which are especially dangerous in political regimes undergoing transition.1 Some authors agree that during transition to a new regime, the presidential form of government (as an alternative to deposed dictatorship) makes it harder to consolidate democracy, while the parliamentary (or parameterized semi-presidential form) leads to stronger democracy. I have already written that today political institutionalization and consolidation of political regimes pose a greater challenge for the Soviet successor-states than making the transition from authoritarianism to democracy. In other words, they must achieve political stability and manageability.2 None of the post-Soviet political regimes of the CIS countries can be described as a consolidated democracy. They differ in “the presence or absence of consolidation and stability of their political regimes.”3It seems that the Central Asian region is more vulnerable than the rest of the post-Soviet expanse to threats to political consolidation: there are too many pending social, economic, demographic, environmental, and ethnic problems. The list is longer still: zero experience of pre-Soviet statehood; no consensus among the states on border issues; politicization of Islam; the threat of terrorism; and having an unstable Afghanistan as its closest neighbor. This explains why some authors look at the five Central Asian states as a homogenous entity, while the degree of manageability and the extent of regime consolidation differ from country to country.Political institutionalization is the most important single factor of regime stability interpreted as rationalizing (Max Weber) political institutions as sustainable, meaningful, and reproducible forms of behavior. The level of political institutionalization “is the extent to which political organizations and procedures exist independently of other social groupings” (the family, clan, or class) or an individual.4